PENGARUH PENERAPAN ETIKA BISNIS ISLAM TERHADAP KINERJA USAHA MIKRO KECIL DAN MENENGAH - Ekarina Katmas; Nur Faizah; Ayu Wulandari (Jurnal Asy-Syukriyyah, 2022)
This research aims to determine the extent of the influence of the application of Islamic business ethics on the performance of Small and Medium Enterprise (SME). The research method used in this research is quantitative research with multiple linear regression analysis based on multiple linear regression analysis obtained partial and simultaneous effect. The results of the accepted hypothesis or variables that have a positive and significant effect on the performance variables, namely the aspect of fairness, free will, responsibility, Tauhid and Ihsan have a significant positive effect on the performance of Small and Medium Enterprise (SME). Simultaneously all aspects of Islamic business ethics affect performance with a coefficient of determination of 0.746 or 74.6%. The independent variable that has the most dominant influence on performance is seen from the Standardized Coefficients Beta test by looking at the value of the Standardized Coefficients Beta the largest is the responsibility variable with a value of 0.475 greater than the other variables.